กายวิภาคศาสตร์เปรียบเทียบก้านใบย่อยของไม้ต้น 6 ชนิด ในสกุล Dalbergia (Fabaceae) - สุวรรณรัตน์ วรางคณา; อุทัยรัศมี สุวิมล; เกื้อมณี ประศาสตร์ (Thai Journal of Science and Technology, 2020)
Many tree species in the genus Dalbergia are valuable woods and used as a source of luxury furniture and flooring. However, some species have very similar morphological characteristics. In this case, the floral parts are the key trait for identification of those species. However, flowering time of the year can be problematic due to not present flowers all year round. Petiolule, on the other hand, is more practical in terms of specimen collection. The objective of this research was to study the anatomical petiolule structures in 6 Dalbergia tree species distributed in northeastern Thailand, including Dalbergia glomeriflora, D. cultrata, D. lanceolaria var. lakhonensis, D. nigrescens, D. oliveri and D. Cochinchinensis, to make a key identification. The results showed that some differences among all species were found in the presence or absence of trichomes, brown or red ergastic substances in cortical cells, vascular bundle shape and cuticle thickness. Based on these characteristics, an identification key of chosen Dalbergia species was made. In addition, there were no differences in anatomical characteristics in each position of petiolule (proximal, medial and distal). Therefore, the identification key of petiolule characters is one of suitable tools to enhance the taxonomy of this genus.